2007
DOI: 10.1007/s11695-007-9324-7
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Ghrelin Levels After Weight Loss in Obese Zucker Rats is Prevented by Gastric Banding

Abstract: Background Gastric banding is thought to decrease appetite in addition to the mechanical effects of food restriction, although this has been difficult to demonstrate in human studies. Our aim was to investigate the changes in orexigenic signals in the obese Zucker rat after gastric banding. Methods Obese Zucker rats ( fa/fa) were submitted to gastric banding (GBP), sham gastric banding fed ad libitum (sham), or sham operation with food restriction, pair-fed to the gastric banding group (sham-PF). Lean Zucker r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Most importantly, meal suppression of circulating total (Korner et al, 2006;Engström et al, 2007) and acyl (Korner et al, 2005(Korner et al, , 2006 ghrelin was normalized in obese persons after gastric bypass surgery. On the other hand, gastric banding surgery prevented the increase of plasma total ghrelin level after weight loss in obese Zucker rats, which supported the hypothesis that sustained weight loss observed after gastric banding did not depend solely on food restriction (Monteiro et al, 2007). However, restrictive surgery, such as gastric banding, sometimes resulted in increased (Nijhuis et al, 2004;Korner et al, 2009) or unchanged (Hanusch-Enserer et al, 2003 plasma total ghrelin level after operation in humans.…”
Section: Ghrelin Gene Products In Food Intake and Gut Motilitymentioning
confidence: 69%
“…Most importantly, meal suppression of circulating total (Korner et al, 2006;Engström et al, 2007) and acyl (Korner et al, 2005(Korner et al, , 2006 ghrelin was normalized in obese persons after gastric bypass surgery. On the other hand, gastric banding surgery prevented the increase of plasma total ghrelin level after weight loss in obese Zucker rats, which supported the hypothesis that sustained weight loss observed after gastric banding did not depend solely on food restriction (Monteiro et al, 2007). However, restrictive surgery, such as gastric banding, sometimes resulted in increased (Nijhuis et al, 2004;Korner et al, 2009) or unchanged (Hanusch-Enserer et al, 2003 plasma total ghrelin level after operation in humans.…”
Section: Ghrelin Gene Products In Food Intake and Gut Motilitymentioning
confidence: 69%
“…In addition, a cross-sectional study of subjects who had undergone gastric banding 9-15 months previously found that banding patients had significantly lower plasma ghrelin levels than normoweight and obese controls [18]. A recent study of the relationship between LAGB and plasma leptin in obese Zucker rats [22] has suggested that, in a standardized system, ghrelin levels remain constant after surgery. With our study's larger subject group (n=24), assessment of acylated and total ghrelin, and multiple independent measurements of the amount of total ghrelin in each plasma sample, we aimed to decrease variation often caused by small sample size and inter-assay variability.…”
Section: Discussionmentioning
confidence: 99%
“…The band was fixed with two vertical stitches [22,23]. For the control group, the technique consisted of the same procedure described above except for the incision of the stomach.…”
Section: Studies In Ratsmentioning
confidence: 99%